The role of modern manufacturing systems in process Design - Wahab, Zainab Salah (Journal of Economics and Administrative Sciences, 2021)
The aim of the research to measure the correlation relationship between modern manufacturing systems and process design and measure the effect by adopting the regression; the research consists of two main variables, which are modern manufacturing systems and process design; it was applied in the production lines of the General Company for Construction Industries, There is a sample of managers, engineers, technicians, administrators, and some workers were selected to fill the special questionnaire with (70) forms which distributed and (65) were approved suitable for use, For data analysis the correlation coefficient was adopted to measure the relationship and regression analysis to find out the effect, Using (SPSS), So the first hypothesis for the research was rejected, that was stated (there is a correlation relationship between modern manufacturing systems and process design)